2020
DOI: 10.21608/ajps.2020.118379
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Biological Studies on Some Medicinal Plants

Abstract: Biological studies on thirteen ethanolic plant extracts (Rosmarinus officinalis ,Ocimum basilicum , Moringa oleifera, Zingiber officinale, Curcuma longa, Nigella sativa ,Cinnamomum verum ,Salvia officinalis, Lepidium sativum, Foeniculum vulgare, Anethum graveolens, Ficus benghalensis and Cinnamomum camphora) revealed that four of them (Rosmarinus officinalis , Zingiber officinale, Cinnamomum verum and Cinnamomum camphora) were the best active against two bacterial species ; E. coli , S .aureus and one fungus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Previous studies [63,64] reported a higher MIC and MFC of C. longa methanolic extract than ours. Meanwhile, MIC and MFC of Z. officinale Rosc from our study are higher than previously reported results [65,66].…”
Section: Discussioncontrasting
confidence: 90%
“…Previous studies [63,64] reported a higher MIC and MFC of C. longa methanolic extract than ours. Meanwhile, MIC and MFC of Z. officinale Rosc from our study are higher than previously reported results [65,66].…”
Section: Discussioncontrasting
confidence: 90%
“…Following the administration of caffeinated beverages, similar findings in hepatic and pancreatic tissues have been reported by Al Eyrani et al and Al Siddiqui et al respectively. 9,23 This occurrence is crucial to the body's inflammatory response to a substance that could be toxic.…”
Section: Eds Consumption Results In Different Hazardousmentioning
confidence: 99%
“…Along with the functional issues, it also damages the organ's exocrine and endocrine components. 9,10 All the untoward effects on different body organs of the younger generation due to the growing consumption of caffeinated beverages in this age group need to be determined. Various studies have been done to demonstrate and explain the toxic effects of different ingredients of EDs on various body organs.…”
Section: Introductionmentioning
confidence: 99%